Evaluation of Sitodiplosis mosellana (Diptera: Cecidomyiidae) infestation and relationship with agronomic traits in selected spring wheat cultivars in northwestern Montana, United States of America. Issue 5 (20th August 2018) - Echegaray, Erik R.; Barbour, Christopher R.; Talbert, Luther; Stougaard, Robert N.
Abstract: The wheat midge, Sitodiplosis mosellana Géhin (Diptera: Cecidomyiidae), is a serious pest of spring wheat in North America. Currently, most commercial cultivars in the state of Montana, United States of America are susceptible. A study was conducted to assess the variability of adapted spring wheat cultivars to wheat midge infestations. A secondary objective was to determine the relationship between wheat midge infestation levels and spring wheat agronomic traits, including yield, test weight, grain protein, plant height, and heading date. This relationship was determined by evaluating 16 hard red spring wheat cultivars over a six-year period at the Northwestern Agricultural Research Center, near Kalispell, Montana. Levels of infestation had a negative impact on grain yield and test weight. Overall, the average infestation level was 40 larvae/spike with the lowest being observed with "Reeder" and the highest for "Thatcher". Concurrently, "Reeder" had the highest yield, whereas "Thatcher" had the lowest yield and the highest grain protein, demonstrating that wheat midge infestations were positively associated with grain protein. Heading date had a positive association with midge density with higher infestations associated with later maturing cultivars. The economic injury level was estimated at 12 and 20 midge larvae/spike for a market price of USD $0.27 and USD $0.16/kg, respectively.